Improving The Quality Of Television Media Broadcasts In Tackling Free Sex Among Teens - Tary Puspa, Ida Ayu; Warmayana, I Gede Agus Krisna; Mardika, I Ketut; Sintya Wati, Ni Putu Evie (Jurnal Penjaminan Mutu, 2019)
Television media is a means of conveying information and communication to many people or society. The knowledge can be accepted by society quickly. Television Media is a means or tool used as information source, education and entertainment. Teenager is a transition period from children to adults which are 11-24 years old.  Adolescence is known for a time full of flaming, indecision, and a great sense of curiosity so need extra control from all of parties, especially their parents and educators. Teenagers today are much influenced by promiscuity such as fee sex. Television media has a variety of programs show that interesting to children and teenagers have a variety of impacts in both positive and negative life especially for teenagers who use television media. Today television shows much of violence contents and promiscuity affect the viewing teenagers and the show intersect with the values and social norms in society. Here are some of the television media roles in tackling free sex in among teenagers, they are: Television is as society education media and used of television in teenager?s life. Television media can be used as one of popular education media of people. Television media can act as an education media by watching the educative show for society. The show that educates be followed by teenagers need getting assisted parents which is able to direct the educative show for their children. The roles of parents, society, education institution have important roles in giving education and directiving so education about sex is not taboo to be learned.Television attracts good interest to adult especially to children and teenagers who like to watch television because it interesting shows and programs and how to present them in a fun way. Television is used by teenagers as entertainment and knowledge media where teenagers can get information quickly and easily.